Hungarian Monitoring, 28 April 1989 . [Magyar rádiófigyelő], 1989. április 28 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - No change in American position on short range missiles - Paris paper "Liberation" on Hungarian TV broadcast of Dubcek interview - Chinese leadership and the student protests - Soviet historian Roy Medvedev a comrade once again Domestic Affairs: - Presidential council and ministerial council decide on dismissals and appointments - Interior Ministry hands over documents of trial of Imre Nagy and colleagues to chief prosecutor - Danube Circle sends open letter to president of Hungarian TV to allow Gabčíkovo-Nagymaros dam inspectors' arguments to be heard, and demand broadcast of Béla Balázs Studio documentary film "Dunasaurus" Economy: - National Association of Entrepreneurs (VOSZ)'s economic concepts - Academic Iván T. Berend thinks that the entrepreneurial strata will be the motor of Hungarian economic development over the next three years Külpolitika: - Nem változott az amerikai álláspont a rövid hatótávolságú rakéták kérdésében - A párizsi Liberation a magyar TV Dubcek interjújáról - A Kínai vezetés és a diáktüntetések - Újra elvtárs Roj Medvegyev szovjet történész Belpolitika: - Felmentésekről és kinevezésekről döntött az ET és a Minisztertanács - A belügyminisztérium átadta Nagy Imre és társai perének iratait a legfőbb ügyésznek - A Duna-kör nyílt levélben kérte a Magyar TV elnökét, hogy adjon lehetőséget a bős-nagymarosi vízi erőmű ellenőreinek érveik kifejtésére, követelik Balázs Béla Duna-Saurus című dokumentumfilmjének bemutatását is Gazdaság: - A VOSZ gazdasági koncepciója - Berend T. Iván akadémikus szerint a következő három évben a vállalkozói réteg lesz a magyar gazdasági kibontakozás motorja